O ingresso e a formação acadêmica do sujeito surdo: singularidades, conquistas e desafios da educação inclusiva no espaço universitário - Silva, Reginaldo Aparecido (2019)
This study had as research problem the factors that hinder the entry, permanence and formation of deaf people in higher education. Its general objective was to know and understand the trajectory of these people regarding their entry and academic education, as well as their achievements and challenges in the university space from the perspective of inclusive education. The theoretical basis is based on authors who bring concepts about the education of deaf people, authors that guide the concepts of inclusion, in addition to the main legal provisions in force, public policies that address the rights and accessibility of people with deafness as well as People with Disabilities (PwD). The research subjects were 07, among undergraduate students and graduates from higher education, aged between 24-45 years, of both sexes, residing in the states of Minas Gerais and São Paulo. The methodological foundation has its genesis in qualitative research supported by the principles of Qualitative Epistemology and the methodological procedures for the production of constructiveinterpretive knowledge. For the production of the information was used an interview script, instrument consisting of 10 video questions entirely in Sign Language (LS) and subtitled in Portuguese (LP), and answers recorded on video. After the interviews, the analysis of the information took place from the reproduction of the recorded videos, their transcriptions in LP and the appropriation of the signs as well as their meanings, with the purpose of highlighting the pre-indicators as a connection to the construction and organization. of the nuclei of meaning. The indicators were fundamental and presented the real challenge of the subjects to survive in the university space. The results show that the barriers faced in this space are not restricted to the linguistic barrier, but also by the attitudinal barrier. It was possible to foster a reflection on inclusive education regarding its academic challenges. Their experiences and relevant perceptions regarding this context presented us with the challenges and exclusionary conditions they experienced, and pointed us to at least two factors: indifference and disrespect. From the participants expressions, it was possible to understand and affirm that the need for paradigm change is emerging. It is concluded that the condition of deaf university students is still challenging, since several mechanisms and exclusionary factors hinder their full inclusion due to the lack of acceptance and respect for their specificities and alterities. To break the barriers of formalism and change the paradigm, the doors to a quality and equitable formation must contemplate respect for human diversity, learning and the development of the potentialities of ALL, regardless of their sociocultural differences.